Nahdlatul Ulama dan Program Moderasi Beragama - Rochmawati, Nur Anis (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: Religious moderation as a religious deradicalization program formulated by the Ministry of Religion, in the public domain, has raised concerns from several parties that it will become a practice of power and domination. Starting from this, this article attempts to examine the central role of Nahdlatul Ulama in the construction of official discourse on the religious moderation program. After reading two documents, the book Religious Moderation and the Roadmap for Strengthening Religious Moderation, this article concludes that the strategic position of Nahdlatul Ulama (NU) cadres in the Ministry of Religion is a quite logical reason why the principles that NU always promotes become key terms in the construction of official discourse on religious moderation programs.